OPTIMALISASI PERAN GURU DAN SANTRI DALAM MENINGKATKAN PENGETAHUAN PERILAKU HIDUP SEHAT TERKAIT COVID-19 - Lucky Prasetiowati; Maftuchah Rochmanti; Dewi Ratna Sari; Dimas Bathoro Bagus Pamungkas; Maya Rahmayanti (Jurnal Layanan Masyarakat (Journal of Public Services), 2021)
AbstractCorona Virus Disease (COVID-19) is a global health problem because it has spread in more than 200 countries in the world, including Indonesia. COVID-19 is caused by the SARS-CoV-2 virus which is transmitted via droplets from infected people. The implementation of optimal health protocols is considered as one of the effective way to break the chain of COVID-19 transmission in Indonesia. Currently, Islamic boarding schools are starting to return their activities by implementing health protocols in the midst of the COVID-19 pandemic. In addition, healthy lifestyle behaviors such as physical activity and balanced nutritional intake related to body immunity are also important in preventing COVID 19. Information on this is still limited, including for boarding school residents as an effort to prevent COVID 19. Teachers and students as an active components in Islamic boarding schools have a big role in preventing the risk of COVID-19 transmission. The purpose of this community service activity is optimize the role of teachers and students in increasing knowledge of healthy lifestyles and immunity related to COVID-19. The method used is online health education and training on making e-posters to teachers. Then there is a transfer of knowledge from teachers to students regarding the material provided is followed by offline discussions. Students were asked to make health promotion media or e-posters for the public and competed. The results of the e-posters competition were disseminated to the pesantren environment. Pre-test and post-test activities were carried out to assess teacher knowledge before and after receiving health education. As a result, there is an increase in knowledge and changes in teacher behavior related to the material provided, namely health protocols, healthy living behavior, balanced nutritional intake and physical activity.Keywords: COVID-19, Islamic boarding school, healthy lifestyle, public health, teacher training.AbstrakCorona Virus Disease (COVID-19) merupakan salah satu masalah kesehatan global karena telah menyebar di lebih dari 200 negara di dunia termasuk Indonesia. Penyakit ini disebabkan oleh virus SARS-CoV-2 yang menular via droplet individu yang terinfeksi. Penerapan protokol kesehatan yang optimal dianggap sebagai salah satu cara efektif memutus rantai penularan COVID-19 di Indonesia. Saat ini pondok pesantren mulai beraktivitas kembali dengan menerapkan protokol kesehatan di tengah pandemi COVID 19. Selain itu perilaku hidup sehat seperti aktivitas fisik dan asupan gizi seimbang yang terkait dengan imunitas tubuh juga penting dalam pencegahan COVID 19. Informasi mengenai hal ini masih terbatas termasuk juga untuk warga pesantren sebagai upaya pencegahan COVID 19. Guru dan santri sebagai komponen aktif di pesantren memiliki peranan besar dalam mencegah risiko penularan COVID-19.  Tujuan kegiatan pengabdian masyarakat ini untuk meningkatkan pengetahuan dan mengoptimalisasi peran guru dan santri dalam meningkatkan pengetahuan pola hidup sehat dan imunitas terkait COVID-19 melalui. Metode yang digunakan adalah penyuluhan kesehatan dan pelatihan pembuatan e-poster kepada guru secara daring. Kemudian dilakukan transfer of knowledgedari guru ke santri mengenai materi yang diberikan diikuti diskusi secara luring. Santri diminta untuk membuat media promosi kesehatan berupa e-poster untuk masyarakat awam dan dikompetisikan serta hasil e-poster di diseminasi ke lingkungan pesantren. Dilakukan kegiatan pre-test dan post-test untuk menilai pengetahuan guru sebelum dan setelah mendapatkan penyuluhan kesehatan. Hasilnya, terdapat peningkatan pengetahuan dan perubahan perilaku guru terkait materi yang diberikan yaitu protokol kesehatan, perilaku hidup sehat, asupan gizi seimbang dan aktivitas fisik.Kata Kunci: COVID-19, pesantren, gaya hidup sehat, kesehatan masyarakat, pelatihan guru.